2015
DOI: 10.1111/1471-0528.13298
|View full text |Cite
|
Sign up to set email alerts
|

First trimester maternal serum biochemical markers of aneuploidy in pregnancies with abnormally invasive placentation

Abstract: Objective To examine whether differences exist in routine first trimester maternal serum screening analyte measurements between normal pregnancies, placenta praevia and abnormally invasive placentation (AIP). Design Multidisciplinary audit.Setting Associated university teaching hospital with 9000 annual deliveries.Population Five hundred and sixteen pregnancies in total, including 344 normal controls, 17 with AIP and 155 placenta praevia cases.Methods Comparison of maternal serum free bhCG and PAPP-A MoMs dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Several placental and fetal hormones routinely used in the screening of Down syndrome have been found to have different concentrations in the serum of women with placenta previa accreta compared with those with a non‐accreta previa . At 11–12 weeks of pregnancy, human chorionic gonadotropin (hCG) and its free beta‐subunit (β‐hCG) are lower and pregnancy‐associated plasma protein A (PAPP‐A) is higher in the maternal serum of women with PAS disorders.…”
Section: Prenatal Screening For Pas Disordersmentioning
confidence: 99%
“…Several placental and fetal hormones routinely used in the screening of Down syndrome have been found to have different concentrations in the serum of women with placenta previa accreta compared with those with a non‐accreta previa . At 11–12 weeks of pregnancy, human chorionic gonadotropin (hCG) and its free beta‐subunit (β‐hCG) are lower and pregnancy‐associated plasma protein A (PAPP‐A) is higher in the maternal serum of women with PAS disorders.…”
Section: Prenatal Screening For Pas Disordersmentioning
confidence: 99%
“…The use of ultrasound and MRI in the diagnosis of PAS has been extensively reviewed elsewhere [ 2 , 55 , 56 ]. Several placental and fetal hormones routinely used in the screening for aneuploidy have been found to be differentially expressed in the serum of women with PAS compared with those with placenta previa [ 57 , 58 ]. More recently, there has been increasing interest in the role of cell-free fetal DNA (cffDNA) for screening and diagnosis of PAS.…”
Section: Biomarkersmentioning
confidence: 99%
“…This led to further studies into maternal serum AFP in the setting of a nonanomalous fetus, to investigate any association between elevated second trimester maternal serum AFP and PAS, all of which suggest that increased level of AFP are associated with PAS ( Table 1 ) [ 86 ]. Interestingly, Zelop et al showed that although AFP was elevated in approximately 45% of confirmed PAS cases, the negative controls did not have elevated levels suggesting this test may have a high negative predictive value [ 57 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…α‐Fetoprotein (AFP) is synthesized by the secondary yolk sac and fetal liver. Levels of both hormones differ between women with placenta accreta spectrum (PAS) disorders and those with non‐accreta previa . Second‐trimester maternal serum levels of AFP are increased, and first‐trimester serum β‐hCG is decreased in women with PAS, compared with those with non‐accreta placenta previa.…”
Section: Clinical Characteristics and Hormonal Valuesmentioning
confidence: 99%
“…Levels of both hormones differ between women with placenta accreta spectrum (PAS) disorders and those with non‐accreta previa . Second‐trimester maternal serum levels of AFP are increased, and first‐trimester serum β‐hCG is decreased in women with PAS, compared with those with non‐accreta placenta previa. An increased level of cell‐free β‐hCG mRNA has also been found in the plasma of women with PAS disorder .…”
Section: Clinical Characteristics and Hormonal Valuesmentioning
confidence: 99%